2010
DOI: 10.1080/03014223.2010.501107
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor responses in tuatara

Abstract: Toll-like receptors (TLR) are an evolutionarily-conserved family of pattern recognition receptors that are a key component of innate immune responses. To understand if leukocytes from tuatara (Sphenodon punctatus), an evolutionarily distinct reptile species, expressed TLR, we isolated blood leukocytes from tuatara and analysed their ability to respond to known TLR2, TLR3, TLR4, and TLR7/8 agonists. We found that all tuatara could respond to these agonists but that responses were significantly greater in leukoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 24 publications
0
17
1
Order By: Relevance
“…Burnham, Keall et al [27] also did not detect a seasonal effect on T cell responses when tuatara were tested during adjacent seasons (winter and spring). In contrast, La Flamme, de Thierry et al [36] observed significantly greater responses to toll-like receptor (TLR) agonists by tuatara leukocytes in summer than in winter.…”
Section: Discussionmentioning
confidence: 87%
“…Burnham, Keall et al [27] also did not detect a seasonal effect on T cell responses when tuatara were tested during adjacent seasons (winter and spring). In contrast, La Flamme, de Thierry et al [36] observed significantly greater responses to toll-like receptor (TLR) agonists by tuatara leukocytes in summer than in winter.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, no seasonal effect on T cell responses was detected in captive tuatara tested during winter and spring (Burnham et al 2005). In La Flamme et al (2010) and the present study, summer was the period of increased immune function. Burnham et al (2005) investigated T cell responses during winter and spring and consequently the time between sampling may have been too small to detect any difference in T cell response.…”
Section: Discussioncontrasting
confidence: 77%
“…Wild tuatara were also sampled only during summer and early autumn, therefore the time span between sampling periods may be too small to detect a difference in antibody production. A similar seasonality was observed in responses to toll-like receptor (TLR) agonists by leukocytes, with significantly greater responses observed in summer than in winter (La Flamme et al 2010). In contrast, no seasonal effect on T cell responses was detected in captive tuatara tested during winter and spring (Burnham et al 2005).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations